Mechanistic insights into the role of traditional Chinese medicine in treating gastric cancer - Chen, Ziqiang; Yu, Ting; Wang, Yunhe; Li, Jiaxin; Zhang, Bo; Zhou, Liya (Frontiers in Oncology, 2025)
Gastric cancer remains a leading cause of cancer-related mortality worldwide, with advanced stages presenting significant challenges due to metastasis and drug resistance. Traditional Chinese Medicine (TCM) offers a promising complementary approach characterized by holistic treatment principles and minimal side effects. This review comprehensively explores the multifaceted mechanisms by which TCM addresses gastric cancer. Specifically, we detail how TCM inhibits aerobic glycolysis by downregulating key glycolytic enzymes and metabolic pathways, thereby reducing the energy supply essential for cancer cell proliferation. We examine how TCM suppresses angiogenesis by targeting the vascular endothelial growth factor (VEGF) and cyclooxygenase-2 (COX-2) pathways, effectively starving tumors of nutrients and oxygen required for growth and metastasis. Furthermore, TCM modulates the immune microenvironment by enhancing the activity of effector immune cells such as CD4+ and CD8+ T cells and natural killer (NK) cells while reducing immunosuppressive cells like regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs). These actions collectively contribute to slowing tumor progression, inhibiting metastasis, and enhancing the body’s antitumor response. The insights presented underscore the significant potential of TCM as an integral component of comprehensive gastric cancer treatment strategies, highlighting avenues for future research and clinical application to improve patient outcomes.